Integrasi Kesalehan Sosial dan Ajaran Islam Pada Anak Usia Dini Melalui Dongeng Al-Najm Al-Kabīr Karya Dr. Zahīrah Al-Bailī - Fitriliza Fitriliza; Teguh Luhuringbudi; Panggih Abdiguno (Universitas Muhammadiyah Prof Dr Hamka, 2020)
This paper seeks to see the integrative points of the struggle for Islamic teachings and sosial piety that need to be taught to early childhood based on children's Arabic fairy tales. This study uses two approaches, namely an educational approach and an Islamic approach. The educational approach studied is the application of the Sosial Learning Theory proposed by Albert Bandura in analyzing any binary opposition of good and bad attitudes in each quotation (dialogue or story) of the children's fairy tales studied. The Islamic approach studied is to use the Quranic perspective as a source of human life guidance which is applied to Islamization of the results of Sosial Learning analysis so that good and bad attitudes can be assessed as an important dogmatic reminder instrument in fostering the character of sosial piety and Islamic personality. The use of two approaches as characteristics of interdisciplinary studies in this study leads to primary sources that refer to a children's fairy tale entitled al-Najm al-Kabīr by Dr. Zahīrah al-Bailī. This research concludes that the dogma-lessons of sharing love and affection in early childhood that can be done by loving each other and habituating apologizing if you make mistakes will reflect-stimulate personality in shaping the character of devotion to parents and sosial relationships.